Age Matched Corneal Endothelial Cell Count in Patients with Pseudo Exfoliation Syndrome - Butt, Waqas Rahim; Naqvi, Syed Abid Hassan; Humayun, Fakhar; Ashraf, Ammarah; Ashraf Khan, Taimoor; Sajjad Rathore, Hassan (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate corneal endothelial cell count (CECC) in patients with Pseudo Exfoliation Syndrome (PEX) and control participants of matched age along with comparing intra ocular pressure (IOP) between the two groups.Study Design: Comparative Cross Sectional Study.Place and Duration of Study: Armed Forces Institute of Ophthalmology Rawalpindi, Pakistan from Dec 2022 to May 2023.Methodology: A total of 70 participants were enrolled for this cross-sectional analysis through two matched sample groups which included 35 individuals with Pseudo exfoliation syndrome (PEX) and 35 control subjects without Pseudo exfoliation syndrome. A statistical evaluation compared corneal endothelial cell count using specular microscopy and IOP measurement (by Goldman applanation tonometry) between study groups.Results: The PEX group demonstrated reduced mean Corneal endothelial cell count (CECC) measurements at 1768.29±213.53 cells/mm² compared to control group CECC (2245.89±187.70cells/mm²) with p